ANALISIS PENGENAAN TARIF PAJAK PROGRESIF PADA PAJAK KENDARAAN BERMOTOR BERDASARKAN THE FOUR MAXIMS DI KABUPATEN MINAHASA - Moningka, Novita Asrilia; Saerang, David Paul Elia; Sabijono, Harijanto (GOING CONCERN : JURNAL RISET AKUNTANSI, 2015)
Motor vehicle tax has strong enough role in the aceptance of local revenue. In North Sulawesi progressive tx on motor vehicles is valid from 12 january 2012 based on Law No. 28 of 2009on local taxes and levies, based on the implementation of provincial regulations SULUT number 7 of 2011 concerning local tax applies to both private motor vehicle ownership and so, the two-wheeled vehicles and four-wheel except for a pick and dumb truck. Principles of taxation proposed by adam smith namely equality, certainly, conveinence of payment, efficiency. Research carried out the UPTD Tondano district of Minahasa. The analytical method used is descriptive analysis (qualittive) that analyzes comparing two different aspects of theory and practice which need to be met in order to know the differences. The purpose of this studyÂ  is determineÂ  how the imposition of a progressive tax rate on motor vehicle tax is based on the four maxims. The result showed that the principle of taxation is still apropriate and relevant to be applied to the motor vehicle tax collection.